2016
DOI: 10.1177/0954407016671462
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the contact features on the tyre wear in steady-state conditions

Abstract: This paper focuses on invetigating the relationship between the contact features of the tyres and the tyre wear in a quantitative sense as a function of the tyre structure and the manoeuvre parameters by utilizing a modified theoretical tyre wear model. The modified tyre wear model was developed by combining a modified ring model for the tyres and a modified brush model and was validated. The model parameters were also identified by physical experiments. Moreover, the contact features were characterized as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…If the central value in each category is considered, then the correlation is almost linear. This is consistent with [7,33,34]. A rough approximation can be given as 10 3 67 10 m…”
Section: Traffic Profilesupporting
confidence: 80%
See 1 more Smart Citation
“…If the central value in each category is considered, then the correlation is almost linear. This is consistent with [7,33,34]. A rough approximation can be given as 10 3 67 10 m…”
Section: Traffic Profilesupporting
confidence: 80%
“…However, they may have great impact.  balancing of wheels: imbalances cause increase in W [21]  tire pressure: lower pressure increases W [21,34,37]  temper of driver: 6.2 fold in W between drivers on the same course [33], or 1.4 fold within the same convoy [21] As a consequence, even identical vehicles with identical tires may have different average wear rates. In the study of Gebbe [22], authors identified 4 recurring passenger cars and 3 commercial vehicles with up to 20 units each and compared their wear rate.…”
Section: Other Factorsmentioning
confidence: 99%
“…Non-exhaust airborne particles from traffic are generated from tyre wear, brake wear, and road surface wear, and the resuspension of deposited material that already existed on-road owing to vehicle-induced turbulence (Amato et al, 2011). Each of the non-exhaust airborne particles' sources is closely related to vehicle weight (Simons, 2016;Timmers and Achten 2016;Timmers and Achten, 2018;Wang et al, 2017). The conversion of ICE passenger car to an equivalent EV causes an increase in vehicle weight due to the heavier battery pack compared to an equivalent conventional engine.…”
Section: Mass Estimation Of Icevs and Evsmentioning
confidence: 99%
“…Despite the replacement of asbestos and a gradual elimination of copper in brake pad materials, they have environmental consequences. Wahlström et al (2010 [140]) indicated that the low metallic (LM) pads showed higher friction performance and caused more wear to the rotor than the non-asbestos organic (NAO) pads, resulting in higher mass losses and more concentrations of airborne wear particles. Although there were variations in the measured particle concentrations, similar size distributions of airborne wear particles were obtained regardless of the pad material.…”
Section: Brake Pad Typementioning
confidence: 99%